2011
DOI: 10.1177/0003319711405507
|View full text |Cite
|
Sign up to set email alerts
|

General or Local Anesthesia for Carotid Endarterectomy—The “Real-World” Experience

Abstract: Perioperative complications from carotid endarterectomy (CEA) are the main drawbacks of the procedure. The aim of this study was to assess the complication rates in patients undergoing CEA under general anesthesia (GA) or regional anesthesia (local anesthesia [LA]) at our institution. Patients undergoing CEA at our regional vascular unit between 2000 and 2004 were included. Data were collated retrospectively from a prospective database. Follow-up was up to 62 months. In all, 383 endarterectomies were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Seven nonrandomized studies with one arm's sample size being at least twice as big as the other arm and which had high chances of bias were excluded. 11,12,14,25,27,28,31 The 24 remaining studies were analyzed, yielding similar results: LA was associated with shorter total surgical time (WMD À8.77 min [À16.84 to À0.69]; p = 0.03) ( Supplementary Fig 3), lower stroke rate (OR 0.64 [0.38-0.89]; p = 0.01) ( Supplementary Fig 4), cardiac complications (OR 0.48 [0.32-0.72]; p = 0.004) ( Supplementary Fig 5), 30-day mortality (OR 0.66 [0.45-0.96]; p = 0.03) ( Supplementary Fig 6), and TND rates (OR 0.58 [0.38-0.89]; p = 0.01) ( Supplementary Fig 7). Heterogeneity was significant for total surgical time (I 2 = 0.99, chisquare = 1,214.45; p < 0.00001) and cardiac complications (I 2 = 0.43, chi-square = 29.79; p = 0.03) but not for stroke (I 2 = 0.15, chi-square = 18.88; p = 0.28), TND (I 2 = 0.24, chisquare = 18.33; p = 0.19), and 30-day mortality (I 2 = 0.00, chisquare = 11.72; p = 0.86).…”
Section: Resultsmentioning
confidence: 99%
“…Seven nonrandomized studies with one arm's sample size being at least twice as big as the other arm and which had high chances of bias were excluded. 11,12,14,25,27,28,31 The 24 remaining studies were analyzed, yielding similar results: LA was associated with shorter total surgical time (WMD À8.77 min [À16.84 to À0.69]; p = 0.03) ( Supplementary Fig 3), lower stroke rate (OR 0.64 [0.38-0.89]; p = 0.01) ( Supplementary Fig 4), cardiac complications (OR 0.48 [0.32-0.72]; p = 0.004) ( Supplementary Fig 5), 30-day mortality (OR 0.66 [0.45-0.96]; p = 0.03) ( Supplementary Fig 6), and TND rates (OR 0.58 [0.38-0.89]; p = 0.01) ( Supplementary Fig 7). Heterogeneity was significant for total surgical time (I 2 = 0.99, chisquare = 1,214.45; p < 0.00001) and cardiac complications (I 2 = 0.43, chi-square = 29.79; p = 0.03) but not for stroke (I 2 = 0.15, chi-square = 18.88; p = 0.28), TND (I 2 = 0.24, chisquare = 18.33; p = 0.19), and 30-day mortality (I 2 = 0.00, chisquare = 11.72; p = 0.86).…”
Section: Resultsmentioning
confidence: 99%
“…In most workplaces only one type of anesthesia is chosen according to their practice and tradition. [1][2][3][4][5] We use both anesthetic techniques at our department. The type of anesthesia is always selected individually.…”
Section: Discussionmentioning
confidence: 99%
“…Although both anesthetic procedures are considered equivalent, each presents its own advantages and disadvantages to both surgeon and anesthesiologist as well as to the patient. [1][2][3][4][5] The need for a measure of patient satisfaction and preference regarding GA or LA during CEA was discussed. 6,7 Both GA and LA are used in our department, and the type of anesthesia is chosen on an individual basis.…”
mentioning
confidence: 99%
“…Stoner et al [11] reported a significantly reduced perioperative complication rate associated with use of LA, especially in high-risk patients undergoing CEA. On the contrary, some studies found no significant differences between LA and GA in terms of stroke, death, and myocardial infarction at postoperative 30 days [12][13][14][15]. Surgical strategies including one-or two-stage operations have been suggested to minimize perioperative neurological and cardiac complications [16,17].…”
Section: Discussionmentioning
confidence: 99%